1997
DOI: 10.1111/j.1748-5827.1997.tb03313.x
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid‐stimulating hormone and total thyroxine concentrations in euthyroid, sick euthyroid and hypothyroid dogs

Abstract: Canine thyroid-stimulating hormone (cTSH) was measured in a variety of clinical cases (n = 72). The cases were classified as euthyroid, sick euthyroid, hypothyroid or hypothyroid on nonthyroidal therapy on the basis of their history, clinical signs, laboratory results (including total thyroxine concentrations and, where indicated, thyroid-releasing hormone [TRH] stimulation tests) and response to appropriate therapy. Additional samples were taken during some of the TRH stimulation tests to measure the response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
56
0
5

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(65 citation statements)
references
References 17 publications
4
56
0
5
Order By: Relevance
“…Quando a suspeita clínica do hipotiroidismo é grande e a síndrome do eutiroideo doente é descartada, a mensuração isolada do T4 livre tem um forte valor diagnóstico, pois é o teste que apresenta maior especiϐicidade (94%) e acurácia (95%), quando avaliado isoladamente (Ramsey & Herrtage 1997, Scott-Moncrieff 2010. A média de T4 livre observada em nossa casuística foi de 0,21±0,14ng/dL (VR =0,7-2,6).…”
Section: Quadro 2 Resultados Do Teste Pós-tiroxina (T4t Basal E 6 Hounclassified
“…Quando a suspeita clínica do hipotiroidismo é grande e a síndrome do eutiroideo doente é descartada, a mensuração isolada do T4 livre tem um forte valor diagnóstico, pois é o teste que apresenta maior especiϐicidade (94%) e acurácia (95%), quando avaliado isoladamente (Ramsey & Herrtage 1997, Scott-Moncrieff 2010. A média de T4 livre observada em nossa casuística foi de 0,21±0,14ng/dL (VR =0,7-2,6).…”
Section: Quadro 2 Resultados Do Teste Pós-tiroxina (T4t Basal E 6 Hounclassified
“…Some workers reported precision values very similar or even higher than those obtained in the present study. 3,9 However, other authors reported significantly better precision with the immunoradiometric assay. 13 Only 1 study has been performed using the chemiluminescent assay, and the analytic variability was higher than that obtained in the present study.…”
Section: Discussionmentioning
confidence: 97%
“…8,9,11 For this reason, stimulation tests using thyroid-stimulating hormone (TSH, Thyrotropin) or thyroid-releasing hormone have been proposed. 4,7 Recently, an assay to measure canine TSH has been developed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Igualmente, en niños obesos se encontraron niveles elevados de TSH y una correlación significativa de esta con el índice de masa corporal y los niveles de insulina (Dekelbab et al, 2010). Se debe tener en cuenta que los valores del perfil lipídico (Osorio & Giraldo, 1999;Osorio et al, 2012a) y del perfil tiroideo (Ramsey et al, 1997;Melián-Limiñana et al, 1999;Matamoros et al, 2002;Ramírez-Benavides & Osorio, 2009) pueden ser más bajos que los de otros estudios, y esto se deba posiblemente a la utilización de diferentes técnicas o de diferentes kits para la determinación de cada una de las variables estudiadas.…”
Section: Discussionunclassified